Paliperidone Palmitate and Metabolic Syndrome in Patients With Schizophrenia: A 12-Month Observational Prospective Cohort Study. Issue 3 (June 2016) - Rosso, Gianluca; Pessina, Enrico; Martini, Azzurra; Di Salvo, Gabriele; Maina, Giuseppe
Abstract : Abstract: Oral and long-acting injectable second-generation antipsychotics are known to be associated with a high risk of metabolic adverse effects. Together with other drug treatments, poor lifestyle choices, and genetic liability, they contribute to development of metabolic syndrome (MetS), which occurs in nearly one third of patients with schizophrenia. The primary objective of this multicenter prospective observational study was to explore the prevalence of MetS in a sample of 60 real-world patients treated with paliperidone palmitate (PP) over a period of 12 months. The secondary objectives were to assess other tolerability aspects and the efficacy of PP on schizophrenic symptoms. The proportion of patients with MetS at baseline (33%) did not significantly change neither at 6 (39.0%) nor at 12 months (29.5%) of PP treatment. The same applies to each individual component of MetS. We found a slight but statistically significant increase in body mass index (26.3 ± 6.0 vs 27.1 ± 4.6, P = 0.031) and of waist circumference (98.2 ± 17.9 vs 100.3 ± 15.9, P = 0.021) from baseline to end point. Weight gain was detected in approximately 15% of patients. At least 1 mild or moderate adverse event was found in 71.3%, 88.0%, and 52.1% of patients, respectively, at baseline, 6 months, and 12 months. A significant improvement in schizophrenic symptoms emerged by means of Positive and Negative Syndrome Scale total and subscale scores. Together with previous literature findings, our results seem to indicate that PP could be a valid therapeutic option for patients with a severe disorder and with a high metabolic risk profile.